Minding the marginalized students through inclusion, justice, and hope : daring to transform educational inequities - Lalas, Jose W.; Strikwerda, Heidi Luv; Forlin, Chris; Howard, Tyrone C. (International perspectives on inclusive education, 2021)
While the issue of advancing equity occupies the pages of many education journals across the world and pursuing it in schools and classrooms is a common instructional goal, there is an obvious absence of established school policies combined with pedagogies on how to achieve educational equity. Therefore, equity solution driven by inclusion, justice, and hope is needed to transform the current systemic educational inequities. To ensure and sustain the notion that all children have the opportunities they need to develop, succeed, and meet their potential, it is imperative that we move the discussion about the impact of education from celebrating the academic gain of a few, to the needs of the many marginalized students who are often discounted and dehumanized.